2018
DOI: 10.1021/acsanm.8b01412
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties and Ion Transport in Layered MoS2 Grown by Vapor-Phase Sulfurization for Potential Applications in Nanoelectronics

Abstract: Electronic and dielectric properties of vapor-phase grown MoS2 have been investigated in metal/MoS2/silicon capacitor structures by capacitance–voltage and conductance-voltage techniques. Analytical methods confirm the MoS2 layered structure, the presence of interfacial silicon oxide (SiOx) and the composition of the films. Electrical characteristics in combination with theoretical considerations quantify the concentration of electron states at the interface between Si and a 2.5–3 nm thick silicon oxide interl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 57 publications
6
34
0
Order By: Relevance
“…Endurance and state‐retention tests performed on the devices demonstrate that the observed non‐volatile RS behavior is quite stable over a period despite successive biasing. Comparison of measurements carried out in ambient and vacuum conditions provide plausible arguments that the observed RS effect is due to OH − ions that stem from catalytic splitting of adsorbed water molecules, in agreement with previous findings 36. Analytical simulations support experiments and suggest that the movement of such ions toward (away from) the Si/MoS 2 interface in response to negative (positive) electric‐fields dictates the observed RS behavior by tuning the energy barriers at the interface.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Endurance and state‐retention tests performed on the devices demonstrate that the observed non‐volatile RS behavior is quite stable over a period despite successive biasing. Comparison of measurements carried out in ambient and vacuum conditions provide plausible arguments that the observed RS effect is due to OH − ions that stem from catalytic splitting of adsorbed water molecules, in agreement with previous findings 36. Analytical simulations support experiments and suggest that the movement of such ions toward (away from) the Si/MoS 2 interface in response to negative (positive) electric‐fields dictates the observed RS behavior by tuning the energy barriers at the interface.…”
Section: Resultssupporting
confidence: 87%
“…In the present devices, the observed RS effect can be explained by movement of OH − ions inside the layered MoS 2 . The presence of OH − ions in MoS 2 have been experimentally observed in a previous study through time‐of‐flight secondary ion mass spectroscopy and electrical characterizations 36. There, it was also demonstrated that the OH − ions move presumably along the van der Waals gaps toward (away from) the Si/MoS 2 interface in response to a negative (positive) bias applied on the top electrode 36,37.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…[102] It should be also noted that one method to avoid the formation of wrinkles in 2D materials is to enhance the roughness of the substrate where it is transferred. [105] In ref. [105] In ref.…”
Section: Fabrication Rs Cells Based On 2d Materialsmentioning
confidence: 99%